2016
DOI: 10.1007/s12630-016-0658-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for lung isolation: to block or not to block?

Abstract: In this issue of the Journal, Bussières et al.1 report their findings of a randomized-controlled trial evaluating the use of a bronchial blocker (BB) vs a left-sided double-lumen endotracheal tube (DL-ETT) during video-assisted thoracoscopic surgery (VATS). The focus of their study was on the quality of lung collapse and the time to achieve optimal lung deflation.The authors studied 40 patients requiring one-lung ventilation (OLV) and randomized to receive a BB or a left-sided DL-ETT. The time from opening the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Probably The most important thing is to know which is the best practice in each condition, taking into account the safety of the patient, the need for surgical exposure and the comfort of the anesthesiologist (10). The use of DLT is mandatory in lung isolation and in lung resections involving the main bronchus, while BB is recommended in case of difficult airway management (2, 11), rapid sequence induction, OLV in children, and when postoperative ventilatory support is needed (10). The correct size of the left DLT can easily be derived from the measurement of the left bronchus on CT scan (12).…”
Section: Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably The most important thing is to know which is the best practice in each condition, taking into account the safety of the patient, the need for surgical exposure and the comfort of the anesthesiologist (10). The use of DLT is mandatory in lung isolation and in lung resections involving the main bronchus, while BB is recommended in case of difficult airway management (2, 11), rapid sequence induction, OLV in children, and when postoperative ventilatory support is needed (10). The correct size of the left DLT can easily be derived from the measurement of the left bronchus on CT scan (12).…”
Section: Airway Managementmentioning
confidence: 99%
“…Therefore the division into absolute and relative indications for OLV as has been used to date no longer makes sense; moreover, it is also unpredictable given that a relative indication may become absolute (2,3). In addition to intraoperative hypoxemia, there are other problems that may occur during OLV, which include the mechanical ventila-main bronchus, while BB is recommended in case of difficult airway management (2,11), rapid sequence induction, OLV in children, and when postoperative ventilatory support is needed (10). The correct size of the left DLT can easily be derived from the measurement of the left bronchus on CT scan (12).…”
Section: Introductionmentioning
confidence: 99%
“…We would like to share the experience of our research program on lung collapse during OLV to address this lack in literature. Unlike other studies, our research group has obtained faster lung collapse using BB than DLT, especially when the internal channel of the BB was occluded (9,10). Based on those findings, we (11) demonstrated that a negative pressure develops in the non-ventilated surgical lung after OLV initiation and before pleural opening with both devices.…”
Section: Research Selectionmentioning
confidence: 64%
“…Although we particularly appreciated the history and anatomy sections, we were somewhat disappointed by the sections describing the different techniques that have been used for lung isolation. It seems to us that many other important aspects of lung isolation were omitted from this review, including some studies on alternative lung isolation devices and double lumen endotracheal tubes (DL-ETTs) 2,3 and some of our own work to improve the use of left and right DL-ETTs. 4 For example, in 2001, we published a randomized study challenging the classic technique 5 of positioning left-sided DL-ETTs and proposed a new position and landmark technique based on directly visualizing the carina through the left endobronchial lumen of the DL-ETT.…”
Section: The Evidence Base Surrounding Lung Isolation Often Is Wider mentioning
confidence: 99%
“…(3) the long-term patency of this arteriovenous graft could be equivalent to that of totally arterial grafts thanks to the action onto the intimal layer of the venous component of relaxing factors such as nitric oxide, which are derived from the endothelial cells of the right IMA stump. 3 The need for a good match (size, thickness, and quality of the wall) between the right IMA stump and saphenous vein graft, a higher risk Letter to the Editor / Journal of Cardiothoracic and Vascular Anesthesia 32 (2018) e1-e34 e13…”
Section: Coronary Artery Bypass Grafting Using An Arteriovenous I-conmentioning
confidence: 99%